Effect of serotonin injection on the reproductive parameters and haemolymph methyl farnesoate level in the narrow-clawed crayfish Pontastacus leptodactylus (Eschscholtz, 1823) - Farhadi, Ardavan; Harlioglu, Muzaffer Mustafa; Yilmaz, Okkes (Wiley, 2020)
The effects of serotonin injection (1, 5 and 10 mu g/g body weight) on spermatozoal production, vas deferens index (VDI), hepatosomatic index (HSI), testicular index (TI), gonado-somatic index (GSI), ovarian egg number, total protein, methyl farnesoate (MF) levels of haemolymph, amino acid and fatty acid profiles of hepatopancreas were evaluated in Pontastacus leptodactylus. In male P. leptodactylus, the highest spermatozoal number (9.3 x 10(6) +/- 1.2) and MF level (0.66 +/- 0.06 ng(-1) ml) were observed after injection of 10 mu g/g of serotonin (p <.05). Serotonin injection, however, did not significantly affect the reproductive parameters in female P. leptodactylus ( p > .05). It was also found that serotonin injection caused an increase in the level of MF in male P. leptodactylus but a reduction in female P. leptodactylus (p < .05). Therefore, a sex- dependent response to serotonin could exist for MF synthesis in P. leptodactylus. Serotonin injection did not affect the total protein, amino acid and fatty acid profiles in the hepatopancreas of male P. leptodactylus (p > .05). It can be concluded that serotonin injection affects the reproductive parameters such as spermatozoal production, VDI, TI, GSI, HSI and haemolymph MF levels in P. leptodactylus.
Keywords: Decapoda; hormone; neurotransmitter; reproductive efficiency; spermatozoa